Depiction of Evil in Harry Potter Series - Pospíšilová, Tereza (Univerzita Pardubice, 2025)
This bachelor thesis focuses on the depiction of evil in the Harry Potter book series by J. K. Rowling. It situates the series within the traditions of Children's and Fantasy Literature, analysing its thematic and narrative structures. Furthermore, it explores the various manifestations of evil through key characters, creatures, and magical objects, emphasising their significance within the story.
Zobrazení zla v knihách o Harry Potterovi
Keywords: Harry Potter; zlo; fantasy literatura; dětská literatura; kouzelník; magie; Harry Potter; evil; Fantasy Literature; Children's Literature; wizard; magic